“La cultura organizacional y su relación con el comportamiento de los trabajadores de la empresa de telecomunicaciones Best Cable” - Vallejos Mendoza, Karin Elizabeth (2019)
ABSTRACT All the organizations have its own culture which define them. In some organizations, there is a strong culture and others are vulnerables, as “Best Cable” Telecommunications Company’s case. This work outline the organizational culture's study, but considering the less visible elements, which means from an immaterial dimension. Additionally, this work permits us to know about workers' behavior therefore we can do the following question: What is the relationship between organizational culture, in an immaterial dimension with the workers' behavior into "Best cable" telecommunications company? This question have the objective to determine if there is an interrelationship between both variables. As well, we could identify the organizational culture's components in its immaterial dimension which was related with the works' behavior; the "Best Cable" workers' behavior was analyzed and finally we known if organizational culture influence into workers' behavior. In order to obtain results, we used instruments such as: Observation guide, interview guide, survey, and analysis document guide. Once, all data was collected, the statistical test 'd de Somers' was applied, in order to know if there was or not a relationship between the variables. That's how the results obtained concluded there is a relationship between organizational culture, in a immaterial dimension with "Best Cable" workers' behavior, with this the hypothesis is accomplished.